Built space - adaptation and space – subject connection in a kindergarten environment (Training and Practice : Journal of Educational Sciences, 2022)
The inner motivation of children is learning. Their lives take place in the present, their focus is on the events of the moment. They are constantly adapting to the world around them, meaning they are instinctively “grow” the space. Learning is ideal for an aesthetically pleasing and emotionally comfortable, flexibly changing environment where the spatial world can help a child’s physical, mental and emotional development. The dissertation provides an overview of the architectural and interior design tools that can be used to help the acquisition and application of appropriate spatial mental operations in a preschool environment. It deals with the spatial-material relations that develop the body scheme and personal physical space, as well as spatial orientation. It also examines the spatial structures that stimulate movement and the toys, objects, equipment, and furniture that focus on the development of the senses.
Keywords: perception; body awareness; spatial perception; orientation; use of square